Neuroscience of psychoactive substance use and dependence (World Health Organization, 2004)
This neuroscience report attempts to provide a comprehensive overview of the biological factors related to substance use and dependence by summarizing the vast amount of knowledge gained over the last 20 - 30 years. The report highlights the current state of knowledge of the mechanisms of action of different types of psychoactive substances, and explains how the use of these substances can lead to the development of dependence syndrome. Though the focus is on brain mechanisms, the report also addresses the social and environmental factors which influence substance use and dependence. It also deals with neuroscience aspects of interventions and in particular the ethical implications of new biological intervention strategies.